Cocoa growing in the tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Farming World Service. PO Box 294, Ikom, Cross River State, Nigeria Naira 250 for ACP orders; Naira 400 for others (incl. p+p) Email: farmingworld2000@yahoo.com For PDS subscribers in Ghana and Cameroon only: CTA Number 1024. 5 credit points